Recognizing the Propensity for Burnout During Formative Counsellor Development - Cieslak, Damian (Canadian Journal of Counselling and Psychotherapy, 2016)
Burnout is one of many hazards that counsellors and psychologists face in their daily work. Working in the counselling field in the modern era can also create the perfect storm of circumstances leading to burnout. Typical client population characteristics, common working environments, and current societal pressures may all lead to increased susceptibility to burnout. Graduate students, in particular, must recognize how these factors, the process of counsellor development, and the concurrent demands of graduate education may each exacerbate the hazard for burnout. Suggestions for mitigating the opportunities for burnout at the institutional and individual levels are also provided.